1977
DOI: 10.1159/000231917
|View full text |Cite
|
Sign up to set email alerts
|

Surface Characteristics of the Human K (Killer) Lymphocyte

Abstract: The human non-allergized K (killer) lymphocyte has been characterized using selective depletion and isolation procedures based on surface markers. It was found to be a non-thymus-dependent, Fc-receptor-bearing cell. In an area which is controversial, our findings also indicate that the cell has immunoglobulin on its surface but lacks the receptor for the C3 component of complement (mouse). This would suggest it to be an (Fc + C3––) B lymphocyte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The percentage of (Fc)IgG-receptor C3-receptor-and Ig-bearing subsets were comparable to the values determined for the small cells as a whole or within each tumour preparation. As with the small cells, some rosettes (25 + 27%) were formed with control indicator cells in the DARR assay (Coombs et al, 1977) suggesting a macrophage-like reactivity. Many of the rosetting cells (20-60%) resembled macrophages morphologically, but it was not possible, because of the (Table II) prepared either by mechanical disaggregation or by short-term collagenase digestion.…”
Section: Lymphoreticular Cells In Human Brain Tumoursmentioning
confidence: 74%
See 3 more Smart Citations
“…The percentage of (Fc)IgG-receptor C3-receptor-and Ig-bearing subsets were comparable to the values determined for the small cells as a whole or within each tumour preparation. As with the small cells, some rosettes (25 + 27%) were formed with control indicator cells in the DARR assay (Coombs et al, 1977) suggesting a macrophage-like reactivity. Many of the rosetting cells (20-60%) resembled macrophages morphologically, but it was not possible, because of the (Table II) prepared either by mechanical disaggregation or by short-term collagenase digestion.…”
Section: Lymphoreticular Cells In Human Brain Tumoursmentioning
confidence: 74%
“…In contrast to our findings, were not able to detect C3-receptor-bearing macrophages. These authors, on the other hand, used trypsin to prepare their tumour cell suspensions-a procedure known to readily remove C3 receptor from the cell surface (Eremin et al, 1977). Macroglial cells (Glees et al, 1978) and tumour cells (Kerr & Searle, 1972) have been documented expressing phagocytic activity, and therefore could possibly possess surface receptors for Fc and C3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A clear definition of the nature of lymphocyte sub sets responsible for ADCC in different spe cies has been the goal of many investigators (4, 7, 12-14, 21, 28, 31, 39, 40], Some of the earlier studies had claimed that lym phoid K cells possess B cell characteristics [9,42,44] but the bulk of evidence favors the hypothesis that a null lymphocyte (e.g., neither B nor T) is the predominant K cell in most species. However, some recent stud ies have suggested that T cells may act as K cells against some targets [5,11,20,28,37,38], and the human B cell was clearly shown to act as a K cell against lymphoblastoid cell targets by Eremin et al [7].…”
Section: Introductionmentioning
confidence: 99%